A Meta-Analysis Evaluating the Colchicine Therapy in Patients With Coronary Artery Disease - Grajek, Stefan; Michalak, Michał; Urbanowicz, Tomasz; Olasińska-Wiśniewska, Anna (Frontiers in Cardiovascular Medicine, 2021)
Background: Evidence from recent studies has shown the benefits of colchicine for patients with coronary artery disease. The aim was to assess the effect of colchicine treatment on cardiovascular events, with an estimation of the risk of discontinuation and net clinical benefit. Methods and Results: Fourteen trials with a total of 13,186 patients were selected through a systematic search. Colchicine therapy significantly reduced the relative risk of primary endpoint by about 30% [RR 0.70 (95%CI:0.56–0.88)]. Compared with placebo, colchicine significantly reduced the risk of ischemia-driven revascularization [RR 0.57 (95%CI 0.41–0.80)], ischemia-driven revascularization and resuscitation [RR 0.50 (95%CI 0.34–0.73)], myocardial infarction [RR 0.73 (95%CI 0.57–0.95)], and stroke [RR 0.49 (95%CI 0.30–0.7)]. Patients treated with colchicine in comparison with placebo have a significant increase in the risk of treatment cessation (RR 1.60 95%CI 1.06–2.42). However, in the analysis which excluded studies without placebo, the relative risk of discontinuation was smaller (RR 1.34 95%CI 0.97–1.84) and in the three largest studies, the risk of discontinuation was lower and insignificant [RR 1.26 (95%CI 0.87–1.83)]. The net clinical benefit was 17.8/1,000 patients (p < 0.001). Conclusion: In coronary artery disease, low-dose colchicine significantly reduces the risk of the primary composite endpoint by about 30%. The drug should be considered as part of the preventive treatment in patients with good tolerance.